Analysis of tattoos in an autopsy population: A two-year study - Bardale, Rajesh; Ninal , Nitin (Journal of Indian Academy of Forensic Medicine, 2021)
Traditionally tattoos have forensic significance for the establishment of identity. Additionally, they can provide information  regarding the religion, culture, lifestyle, region, history, war, occupation, sex interest, gang members and drug abuse. The aim of the  present study is to examine and analyse the distribution of tattoos in autopsy cases from a forensic point of view. This is a post mortem examination based retrospective study conducted at Department of Forensic Medicine, Government Medical College and  Hospital, Miraj. We examined all available files of inquest papers, autopsy reports and toxicological analysis reports into the death of  people through 1 January 2017 to 31 December 2018. A standard proforma was designed to collect the information to ensure  consistency for the whole sample. Out of the total 1390 autopsies that were conducted, 269 deceased were identified to have at least  one tattoo. The mean age of study population was 42.64 (SD 16.13) years. In 269 cases, 360 tattoos were noted. All tattoos were green  in colour. The present study was able to identify the trends of tattoos based on autopsy cases from India.
Keywords: Tattoo; Identification; Autopsy; Death; Forensics